Congenital lumbar hernia associated to lumbar costovertebral syndrome. A case report. - Zoe Quintero Delgado; Guillermo Cortiza Orbe; Yusimy Izaguirre Martínez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2005)
Reported the case of a born patient of color of white skin, 6 years old, of pregnancy and normal childbirth that it was valued in the Service of Surgery of the Pediatric Hospital ¨Paquito González Cueto¨ because it presented increase of volume in both lumbar regions, without another associate sintomatology. Congenital bilateral lumbar hernia associated to syndrome lumbocostovertebral, strange affection in the pediatric age.